Strategies to Address English Language Writing Challenges Faced by International Graduate Students in the US - Ravichandran, Swathi; Kretovics, Mark; Kirby, Kara; Ghosh, Ankita (Journal of International Students, 2018)
Since 2000, there has been a 72% increase in the number of international students attending US institutions of higher education. The increase, specifically of international graduate students, has brought to light the writing challenges experienced by this population of students. This study explored specific writing challenges experienced by international graduate students and determined strategies to alleviate these challenges. Interviews were conducted with 15 international graduate students representing a variety of geographic backgrounds and disciplines. Responses revealed that writing challenges faced related to grammar and vocabulary, organization and flow of ideas, critical thinking, and plagiarism. Participants offered specific suggestions on how subject-matter faculty, friends, and peer mentors could assist in improving English-language writing skills. Implications for higher education institutions are discussed.